Linda di Chamounix melodramma (semiserio) in three acts - Donizetti, Gaetano 1797-1848 (Dynamic Srl., 2021)
Linda di Chamounix, daughter of Antonio, a poor farmer is sought after by the Marchese di Boisfleury, who had been approached for help by Linda's father. Linda, however, is secretly in love with Carlo, whom she knows as a poor painter, but who in reality is the Visconte di Sirval, a nephew of the Marchese
Aufnahme: Teatro del Maggio Musical Fiorentino, 15. Januar 2021
Bildformat: 16:9
Keywords: Operas; Film; Blu-Ray-Disc